The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.18632/oncotarget.17931
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative to post-operative serum carcinoembryonic antigen ratio is a prognostic indicator in colorectal cancer

Abstract: We explored the prognostic significance of the pre-operative-to-post-operative serum carcinoembryonic antigen (pre-post-CEA) ratio in colorectal cancer (CRC). We detected pre- and post-operative CEA levels in 2035 CRC patients surgically treated at First Affiliated Hospital of Zhengzhou University between June 2001 and June 2011. Univariate analysis revealed the pre-post-CEA ratio is associated with distant metastasis and degree of tumor differentiation (both P < 0.05). Multivariate analysis showed that the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Data from a very recent study of 2,035 surgically-treated colorectal cancer patients showed that the pre/post-CEA ratio is associated with lymphatic and distant metastasis, tumor stage, differentiation, and overall survival. 33 Carcinoembryonic antigen monitoring was found to result in better survival outcomes than detection by self-report in patients with recurrent colorectal cancer. 34 This study revealed that blood CEA levels ≥5 ng/mL prior to initiation of oxaliplatin-based chemotherapy were significantly associated with poorer response to chemotherapy and worse overall survival in patients with metastatic colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Data from a very recent study of 2,035 surgically-treated colorectal cancer patients showed that the pre/post-CEA ratio is associated with lymphatic and distant metastasis, tumor stage, differentiation, and overall survival. 33 Carcinoembryonic antigen monitoring was found to result in better survival outcomes than detection by self-report in patients with recurrent colorectal cancer. 34 This study revealed that blood CEA levels ≥5 ng/mL prior to initiation of oxaliplatin-based chemotherapy were significantly associated with poorer response to chemotherapy and worse overall survival in patients with metastatic colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of IL −6 (Thermo Fisher Scientific, Minneapolis, MA, USA), TGF -β1 (Abcam, Cambridge, MA), TNF -α (Abcam, Cambridge, MA) and IL-8 (Thermo Fisher Scientific, USA) were measured by enzyme-linked immunosorbent assay (ELISA) as previously described. 17…”
Section: Enzyme-linked Immunosorbent Assaymentioning
confidence: 99%
“…In our subgroup analysis, we found RAP1A expression in primary CRC tissues could stratify the clinical outcome of both stage II and III patients, suggesting RAP1A as a promising prognostic indicator for identifying risk population within the same TNM stage. Since serum CEA is the most commonly detected parameter for CRC patients and numerous studies have proved the prognostic significance of its preoperative level, we next combined RAP1A expression with preoperative CEA level in prognostic evaluation [ 29 31 ]. As a result, we found high operative CEA level combined with high RAP1A expression was significantly associated with worse clinical outcome in CRC patients as compared with other phenotypes, and this association remains to be statistically significant in the subgroup analysis, except for OS in stage III patients.…”
Section: Discussionmentioning
confidence: 99%